Association of Preoperative NANOG-Positive Circulating Tumor Cell Levels With Recurrence of Hepatocellular Carcinoma - Lei, Yongrong; Wang, Xishu; Sun, Heng; Fu, Yuna; Tian, Yichen; Yang, Ludi; Wang, Jianhua; Xia, Feng (Frontiers in Oncology, 2021)
Background: Cancer stem cells (CSCs) and Circulating tumor cells (CTCs) have been proposed as fundamental causes for the recurrence of hepatocellular carcinoma (HCC). CTCs isolated from patients with HCC illustrate a unique Nanog expression proﬁle analysis. The aim of this study was to enhance the prediction of recurrence and prognosis of the CTC phenotype in patients with HCC by combining Nanog expression into a combined forecasting model. Subjects, Materials, and Methods: We collected 320 blood samples from 160 patients with HCC cancer before surgery and used CanPatrol™ CTC enrichment gathering technology and in situ hybridization (ISH) to enrich and detect CTCs and CSCs. Nanog expression in all CTCs was also determined. In addition, RT-PCR and immunohistochemistry were used applied to study research the expression of Nanog, E-Cadherin, and N-Cadherin in liver cancer tissues and to conduct clinical correlation studies. Results: The numbers of EpCAM mRNA+ CTCs and Nanog mRNA+ CTCs were strongly correlated with postoperative HCC recurrence (CTC number (P = 0.03), The total number of mixed CTCS (P = 0.02), and Nanog> 6.7 (P = 0.001), with Nanog > 6.7 (P = 0.0003, HR = 2.33) being the most crucial marker. There are significant differences in the expression of Nanog on different types of CTC: most Epithelial CTCs do not express Nanog, while most of Mixed CTC and Mesenchymal CTC express Nanog, and their positive rates are 38.7%, 66.7%, and 88.7%, respectively, (Fig. 3B, P=0.0001).Moreover, both CTC (≤/> 13.3) and Nanog (≤/>6.7) expression were significantly correlated with relevant with BCLC stage, vascular invasion, tumor size, and Hbv-DNA (all P < 0.05). In the young group and the old group, patients with higher Nanog expression had a higher recurrence rate. (P < 0.001). Conclusions: The number of Nanog-positive cells showed positive correlation with the poor prognosis of HCC patients. The detection and analysis of CTC markers (EpCAM and CK8, 18, CD45 Vimentin,Twist and 19) and CSCs markers (NANOG) are of great value in the evaluation of tumor progression., the development of tumor drugs, and the monitoring of disease process in cancer patients.